Stable Carbon Isotope Fractionation of Trichloroethylene Oxidized by Potassium Permanganate Under Different Environmental Conditions - Yaqiong Dong; Yufeng Wang; Lantian Xing; Ghufran Uddin; Yuanxiao Guan; Zhengyang E; Jianjun Liang; Ping Li; Changjie Liu; Qiaohui Fan (Applied Sciences)
Stable isotope analysis is a powerful tool for inferring and quantifying transformation processes, but its effectiveness relies on understanding the magnitude and variability of isotopic fractionation associated with specific reactions. Potassium permanganate (KMnO4) is widely used as an efficient oxidant for the degradation of trichloroethylene (TCE); however, the influence of environmental factors on the isotope fractionation during this process remains unclear. In this study, compound-specific isotope analysis (CSIA) was conducted to investigate the variability in carbon isotope effects during the KMnO4-mediated degradation of TCE under varying conditions, including initial concentrations of KMnO4 and TCE, the presence of humic acid (HA), pH levels, and inorganic ions. The results showed that the overall carbon isotope enrichment factors (ε) of TCE ranged from −26.5 ± 0.5‰ to −22.8 ± 0.9‰, indicating relatively small variations across conditions. At low KMnO4/TCE molar ratio (n(KMnO4)/n(TCE)), incomplete oxidation and/or MnO2-mediated oxidation of TCE likely resulted in smaller ε. For dense, non-aqueous phase liquid (DNAPL) TCE, which represents extremely high concentrations, the ε value was −13.0 ± 1.7‰ during KMnO4 oxidation. This may be attributed to the slow dissolution of isotopically light TCE from the DNAPL phase, altering the δ13C signature of the reacted TCE and resulting in a significantly larger ε value than observed for dissolved-phase TCE oxidation. The ε values increased with rising pH, probably due to the decrease in oxidation potential (E0) of KMnO4 from pH ~2 to ~12, as well as the emergence of different degradation pathways and intermediates under varying pH conditions. Both SO42− and NO3− slightly influenced the ε values, potentially due to the formation of H2SO4 and HNO3 at lower pH, which may act as auxiliary oxidants and contribute to TCE degradation. A high concentration (50 mM) of HA led to a decrease in ε values, likely due to competitive interactions between HA and TCE for KMnO4, which reduced the effective oxidation of TCE. Overall, the carbon isotope enrichment factors for KMnO4-mediated TCE degradation are relatively stable, although certain environmental conditions can exert minor influences. These findings highlight the need for caution when applying quantitative assessment based on CSIA for KMnO4 oxidation of TCE.